Geochronology, geochemical characteristics, and tectonic significance of the granites, Menghewula, Southern Great Xing’an range - Yue Haixin; Yu Henan; Sun Zhenjun; He Yanping; Yu Yingbo (Open Geosciences)
The Menghewula region in the southern Great Xing’an range is situated in the superposition area of the Paleo-Asian Oceanic metallogenic domain and the Western Pacific Metallogenic Domain. In this study, we carried out petrography, rock geochemistry, zircon U–Pb chronology and Lu–Hf isotope studies. The results show that granite porphyry and biotite adamellite belong to the weakly peraluminous calc-alkaline. Zircons from both rocks are magmatic in origin, with zircon U-Pb ages of 135.60 ± 0.29 Ma and 134.33 ± 0.28 Ma, respectively, and belong to Early Cretaceous granites. The ε Hf(t) of zircons in the two rocks are all positive (4.50–9.34), and they have younger two-stage model ages (595–904 Ma), which indicate that granitic magmatic material may have originated from the newly formed young crustal materials derived from the depleted mantle in Neoproterozoic. These rocks formed in a post-collisional extensional environment, and were influenced by the subduction and rollback of Paleo-Pacific plate. This study provides scientific basis for the relationship between magmatic evolution and mineralization in the region.